Plant-Based Antigen Production Strategy for SARS-CoV-2 Nucleoprotein and RBD and Its Application for Detection of Antibody Responses in COVID-19 Patients - Katerina Takova; Valeria Tonova; Ivan Minkov; Eugenia S. Mardanova; Nikolai V. Ravin; Stanislav Kotsev; Maria Pishmisheva; Gergana Zahmanova (Applied Sciences)
During the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, the development of efficient serological tests for monitoring the dynamics of the disease as well as the immune response after illness or vaccination was critical. In this regard, low-cost and fast production of immunogenic antigens is essential for the rapid development of diagnostic serological kits. This study assessed the plant-based production of nucleoprotein (N) of SARS-CoV-2 and chimeric receptor-binding domain (RBD) of SARS-CoV-2 presented by hepatitis E virus capsid (HEV/RBD) and validation of the plant-derived proteins as diagnostic antigens for serological tests. The target proteins were expressed in and purified from Nicotiana benthamiana plants. The resulting yield of chimeric HEV/RBD protein reached 100 mg/kg fresh weight and 30 mg/kg fresh weight for N protein. The purified N protein and HEV/RBD protein were used to develop an indirect enzyme-linked immunosorbent assay (iELISA) for the detection of antibodies to SARS-CoV-2 in human sera. To validate the iELISA tests, a panel of 84 sera from patients diagnosed with COVID-19 was used, and the results were compared to those obtained by another commercially available ELISA kit (Dia.Pro D. B., Sesto San Giovanni, Italy). The performance of an HEV/RBD in-house ELISA showed a sensitivity of 89.58% (95% Cl: 75.23–95.37) and a specificity of 94.44% (95% Cl: 76.94–98.2). Double Recognition iELISA based on HEV/RBD and N protein is characterized by a lower sensitivity of 85.42% (95% Cl: 72.24–93.93) and specificity of 94.44% (95% Cl: 81.34–99.32) at cut-off = 0.154, compared with iELISA based on HEV/RBD. Our study confirms that N and fusion HEV/RBD proteins, which are transiently expressed in plants, can be used to detect responses to SARS-CoV-2 in human sera reliably. Our research validates the commercial potential of using plants as an expression system for recombinant protein production and their application as diagnostic reagents for serological detection of infectious diseases, hence lowering the cost of diagnostic kits.